Preparation method of crystallization-assisted high-flux nanofiltration membrane

By pretreating the nanofiltration base membrane and interfacial polymerization reaction, a crystal-assisted high-throughput nanofiltration membrane was prepared, which solved the problem of selectivity-permeability compromise of polymer-based nanofiltration membranes, and achieved a high permeability and selectivity nanofiltration membrane.

CN119701658AActive Publication Date: 2025-03-28CHINA AGRI UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411913487.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

Existing polymer-based nanofiltration membranes have inherent limitations in the selectivity-permeability trade-off, and are limited by the polymer matrix chain stiffness and inter-chain spacing, making it difficult to improve permeability flux and selectivity.

Method used

The preparation method of crystal-assisted high-throughput nanofiltration membrane was adopted to form a high-throughput nanofiltration membrane by pretreating the nanofiltration base membrane, using an aqueous solution of sodium hypophosphite and trans-2,5-dimethylpiperazine, and an organic solution of 1,3,5-benzenetriacetic acid chloride.

Benefits of technology

The permeability flux and selectivity of the nanofiltration membrane are improved, high purity water flux and high retention rate are achieved, and the density and stability of the membrane are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701658A_ABST
    Figure CN119701658A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a crystallization-assisted high-flux nanofiltration membrane. The preparation method comprises the following steps: pretreating a nanofiltration base membrane; preparing a salt solution by using sodium hypophosphite; the preparation method comprises the following steps: preparing trans-2, 5-dimethylpiperazine into a trans-2, 5-dimethylpiperazine solution, and mixing a salt solution with the trans-2, 5-dimethylpiperazine solution to prepare a water phase solution; the preparation method comprises the following steps: mixing 1, 3, 5-benzoyl chloride and an n-hexane solvent to prepare an organic phase solution; and putting the pretreated nanofiltration base membrane into a water phase solution, taking out, drying, putting into a low-temperature controlled organic phase solution, carrying out low-temperature interfacial polymerization reaction, taking out, and drying again to obtain the crystallization-assisted high-flux nanofiltration membrane. According to the method disclosed by the invention, trans-2, 5-dimethylpiperazine which is a new water-phase monomer and sodium hypophosphite are introduced as water-phase additives, and meanwhile, the temperature of an organic phase is controlled, so that the interfacial polymerization temperature is controlled, and the crystallization-assisted high-flux nanofiltration membrane is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of separation membrane preparation, and in particular to a method for preparing a crystallization-assisted high-flux nanofiltration membrane. Background Art

[0002] Nanofiltration membrane technology is an emerging technology for separating organic and inorganic salts with a molecular weight of 200Da-1000Da by size sieving and Donnan effect. In order to improve the filtration performance of nanofiltration membranes, many attempts have been made to adjust the physicochemical properties of the nanofiltration membrane surface, such as pore size, surface charge, wettability, and roughness. However, polymer-based membranes have inherent limitations in the selectivity-permeability tradeoff due to the rigidity of the polymer matrix chains and the interchain spacing. Summary of the invention

[0003] In view of this, the embodiments of the present disclosure provide a method for preparing a crystallization-assisted high-flux nanofiltration membrane, which solves the problem in the prior art that polymer-based membranes have inherent limitations in the selectivity-permeability compromise due to the limitations of polymer matrix chain stiffness and interchain spacing.

[0004] To this end, the present invention provides a method for preparing a crystallization-assisted high-flux nanofiltration membrane, comprising the following steps:

[0005] Pretreatment of nanofiltration base membrane;

[0006] Prepare a salt solution with sodium hypophosphite;

[0007] The trans-2,5-dimethylpiperazine is prepared into a trans-2,5-dimethylpiperazine solution, and then the salt solution is mixed with the trans-2,5-dimethylpiperazine solution to prepare an aqueous phase solution;

[0008] Mixing 1,3,5-benzenetricarboxylic acid chloride and n-hexane solvent to prepare an organic phase solution;

[0009] The pretreated nanofiltration base membrane is placed in an aqueous solution, taken out, dried, and then placed in a low-temperature organic solution for low-temperature interfacial polymerization, taken out and dried again to obtain a crystallization-assisted high-flux nanofiltration membrane.

[0010] According to the method for preparing a crystallization-assisted high-flux nanofiltration membrane provided by the present invention, the nanofiltration base membrane is made of polyethersulfone.

[0011] According to the method for preparing a crystallization-assisted high-flux nanofiltration membrane provided by the present invention, the membrane retention molecular weight of the nanofiltration base membrane is greater than 50 KDa and less than 150 KDa.

[0012] According to the method for preparing a crystallization-assisted high-flux nanofiltration membrane provided by the present invention, the pretreatment of the nanofiltration base membrane comprises:

[0013] The nanofiltration base membrane was immersed in deionized water at 15°C-30°C for 48h-98h, and the deionized water was replaced every 6h-12h.

[0014] According to the method for preparing a crystallization-assisted high-flux nanofiltration membrane provided by the present invention, the concentration of the sodium hypophosphite is 0.01wt%-5.00wt%.

[0015] According to the method for preparing a crystallization-assisted high-flux nanofiltration membrane provided by the present invention, the concentration of trans-2,5-dimethylpiperazine is 0.05wt%-1.00wt%.

[0016] According to the method for preparing a crystallization-assisted high-flux nanofiltration membrane provided by the present invention, the concentration of 1,3,5-benzenetricarboxylic acid chloride in the organic phase solution is 0.025wt%-0.25wt%.

[0017] According to the preparation method of the crystallization-assisted high-flux nanofiltration membrane provided by the present invention, the pretreated nanofiltration base membrane is placed in an aqueous solution, taken out and dried, and then placed in a low-temperature organic solution for low-temperature interfacial polymerization reaction, and then taken out and dried again to obtain a crystallization-assisted high-flux nanofiltration membrane, and the temperature of the organic solution is adjusted to -15°C-20°C.

[0018] According to the method for preparing a crystallization-assisted high-flux nanofiltration membrane provided by the present invention, in the step of placing the pretreated nanofiltration base membrane into an aqueous solution, the residence time of the nanofiltration base membrane in the aqueous solution is 2 min-7 min, the time of the interfacial polymerization reaction is 20 s-120 s, and the drying is rubber roller drying.

[0019] According to the preparation method of the crystallization-assisted high-flux nanofiltration membrane provided by the present invention, the crystallization-assisted high-flux nanofiltration membrane is dried again after being taken out, and the time for the re-drying is 0.5min-2.5min, and the temperature for the re-drying is 20℃-80℃.

[0020] The invention provides a method for preparing a crystallization-assisted high-flux nanofiltration membrane, which comprises preparing a pretreated nanofiltration base membrane, an aqueous solution containing trans-2,5-dimethylpiperazine and sodium hypophosphite, and an organic solution containing 1,3,5-benzenetricarboxylic acid chloride, respectively, and then immersing the pretreated nanofiltration base membrane in the aqueous solution so that the nanofiltration base membrane fully adsorbs trans-2,5-dimethylpiperazine and sodium hypophosphite, then taking out the immersed base membrane and removing the surface solution with a rubber roller to make the subsequent interfacial polymerization reaction more uniform, and then immersing it in the organic solution for interfacial polymerization reaction, so that the trans-2,5-dimethylpiperazine adsorbed on the surface of the nanofiltration base membrane is fully in contact with the 1,3,5-benzenetricarboxylic acid chloride in the organic solution and a polymerization reaction occurs at the interface between the two phases, forming a separation layer on the nanofiltration base membrane, and then drying and curing are performed to further crosslink the formed separation layer, thereby improving its density and Stability, a crystallization-assisted high-flux nanofiltration membrane is obtained, and the invention uses trans-2,5-dimethylpiperazine as an aqueous phase monomer to prepare the nanofiltration membrane. The amino group of trans-2,5-dimethylpiperazine has strong reactivity, and the ortho-methyl group can produce a steric hindrance effect to slow down the diffusion of the oil phase to the aqueous phase, and at the same time reduce the reaction rate, thereby forming a thinner separation layer. When sodium hypophosphite is used, the aqueous phase solution can be filled with hypophosphite and sodium ions to slow down the diffusion of organic phase reactants to the aqueous phase through the spatial steric hindrance effect. At the same time, after drying, the solution will reach an oversaturated state, and the sodium hypophosphite will precipitate on the surface of the base membrane to form protrusions. After the interfacial polymerization reaction, the specific surface area of ​​the separation layer formed will increase, thereby improving the permeation flux of the nanofiltration membrane. At the same time, the protrusion is a salt crystal, and the crystal will dissolve when water passes through. After dissolution, a large number of water channels are formed, thereby improving the water mass transfer rate and the permeation flux of the membrane. Using sodium hypophosphite as an aqueous phase additive can have a steric effect on diffusion during the interfacial polymerization reaction, and at the same time, many uneven crystal protrusions are obtained to increase the specific surface area of ​​the membrane separation layer. At the same time, salt crystals are soluble in water to form water channels to improve mass transfer efficiency. Therefore, the method of the present invention can obtain a nanofiltration membrane with high-purity water flux. In the present invention, controlling the temperature of the organic phase solution is to control the temperature of the interfacial polymerization reaction. This process accelerates the acylation reaction rate while reducing the diffusion rate of the organic phase to the aqueous phase; thereby obtaining a thinner separation layer with a higher degree of crosslinking, so that the nanofiltration membrane prepared by the present invention has high water permeability and high selectivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 Shown is a flow chart of a method for preparing a crystallization-assisted high-flux nanofiltration membrane provided by an embodiment of the present disclosure. DETAILED DESCRIPTION

[0023] The following will be combined with the drawings in the embodiments of the present disclosure to clearly and completely describe the technical solutions in the embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure.

[0024] like Figure 1 As shown, the present invention provides a method for preparing a crystallization-assisted high-flux nanofiltration membrane, comprising the following steps:

[0025] S1. Pretreatment of the nanofiltration base membrane.

[0026] Optionally, the nanofiltration base membrane is made of polyethersulfone.

[0027] Optionally, the membrane molecular weight cutoff of the nanofiltration base membrane is greater than 50 KDa and less than 150 KDa, for example, the membrane molecular weight cutoff of the nanofiltration base membrane is 80 KDa or 100 KDa.

[0028] Optionally, pretreatment of the nanofiltration membrane includes:

[0029] The nanofiltration base membrane was immersed in deionized water at 15°C-30°C for 48h-98h, and the deionized water was replaced every 6h-12h.

[0030] S2. Use sodium hypophosphite to prepare a salt solution.

[0031] Optionally, the concentration of sodium hypophosphite is 0.01wt%-5.00wt%, for example, the concentration of sodium hypophosphite is 0.05wt%, 2wt%, 3wt% or 5.00wt%.

[0032] S3. Prepare trans-2,5-dimethylpiperazine into a trans-2,5-dimethylpiperazine solution, and then mix the salt solution with the trans-2,5-dimethylpiperazine solution to prepare an aqueous phase solution.

[0033] Optionally, the concentration of trans-2,5-dimethylpiperazine is 0.05 wt%-1.00 wt%, for example, 0.05 wt%, 0.07 wt%, 0.08 wt% or 1.00 wt%.

[0034] S4. Mix 1,3,5-benzenetricarboxylic acid chloride and n-hexane solvent to prepare an organic phase solution.

[0035] Optionally, the concentration of 1,3,5-benzenetricarboxylic acid chloride in the organic phase solution is 0.025 wt%-0.25 wt%, for example, 0.025 wt%, 0.125 wt%, 0.20 wt% or 0.025 wt%.

[0036] S5. Put the pretreated nanofiltration base membrane into an aqueous solution, take out the nanofiltration base membrane, dry it, and then put it into a low-temperature organic solution to perform a low-temperature interfacial polymerization reaction, take it out and dry it again to obtain a crystallization-assisted high-flux nanofiltration membrane.

[0037] Optionally, in step S5, the temperature of the organic phase solution is adjusted to -15°C-20°C.

[0038] Optionally, in step S5 of placing the pretreated nanofiltration base membrane into the aqueous solution, the residence time of the nanofiltration base membrane in the aqueous solution is 2 min-7 min, the time of the interfacial polymerization reaction is 20 s-120 s, and the drying is performed by a rubber roller.

[0039] Optionally, after taking out in step S5, the membrane is dried again to obtain a crystallization-assisted high-flux nanofiltration membrane, and the time for the second drying is 0.5 min-2.5 min, and the temperature for the second drying is 20° C.-80° C.

[0040] Sodium hypophosphite is an inorganic compound, mainly used as a preservative and antioxidant in the food industry. When sodium hypophosphite is added to the aqueous phase solution, the aqueous phase solution can be filled with hypophosphite and sodium ions, which slow down the diffusion of organic phase reactants to the aqueous phase through the steric hindrance effect. At the same time, after drying, the solution will reach an oversaturated state, and sodium hypophosphite will precipitate on the surface of the basement membrane to form protrusions. After the interfacial polymerization reaction, the specific surface area of ​​the separation layer formed will increase and thus increase the permeation flux of the nanofiltration membrane. At the same time, this protrusion is a salt crystal. When water passes through, the crystal will dissolve. After dissolution, a large number of water channels will be formed to increase the water mass transfer rate and the permeation flux of the membrane. At the same time, the interfacial polymerization reaction is an exothermic reaction. When the temperature of the organic phase is low, it can not only reduce the diffusion rate of the oil phase, but also accelerate the reaction rate of the interfacial polymerization, so as to form a crystal-assisted high-flux nanofiltration membrane with a low thickness and a high degree of cross-linking. Therefore, the addition of low temperature and sodium hypophosphite has excellent application prospects in the preparation of nanofiltration membranes.

[0041] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] Example 1

[0043] Preparation of crystallization-assisted high-flux nanofiltration membranes. All steps below without temperature indication were performed at room temperature.

[0044] (1) A polyethersulfone (PES) membrane with a size of 6 cm × 6 cm and a molecular weight cutoff of 100 KDa was pretreated by soaking it in deionized water for 48 h. The deionized water needed to be replaced every 12 h.

[0045] (2) 0.1 g of sodium hypophosphite was mixed with 99.9 g of deionized water to prepare a salt solution with a sodium hypophosphite concentration of 0.1 wt %.

[0046] (3) 0.2 g of trans-2,5-dimethylpiperazine was mixed with 99.8 g of deionized water to prepare a trans-2,5-dimethylpiperazine solution having a trans-2,5-dimethylpiperazine concentration of 0.2 wt %; the salt solution and the trans-2,5-dimethylpiperazine solution were mixed in equal proportions to prepare an aqueous phase solution having a sodium hypophosphite concentration of 0.05 wt % and a trans-2,5-dimethylpiperazine concentration of 0.1 wt %.

[0047] (4) 0.3 g of 1,3,5-benzenetricarboxylic acid chloride and 199.7 g of n-hexane solvent were mixed to prepare an organic phase solution having a 1,3,5-benzenetricarboxylic acid chloride concentration of 0.15 wt %.

[0048] (5) Adjust the temperature of the organic phase to -5°C; immerse the pretreated polyethersulfone membrane in the prepared aqueous phase solution and take it out after 5 minutes. Dry the residual moisture on the membrane surface with a rubber roller, and then put it into the organic phase solution for interfacial polymerization. Take it out after 0.5 minutes and put it into a 20°C constant temperature drying oven. After 2 minutes, a crystallization-assisted high-flux nanofiltration membrane is obtained.

[0049] The dried crystallization-assisted high-flux nanofiltration membrane was taken out and sealed in a water environment for measurement. The performance of the prepared crystallization-assisted high-flux nanofiltration membrane was tested with pure water, 2000ppm Na2SO4 aqueous solution and 2000ppm Na2SO4 aqueous solution at a pressure of 0.2Mpa. The test results showed that the pure water permeability of the crystallization-assisted high-flux nanofiltration membrane was 35.26L·m-2h-1bar-1, and the retention rate of Na2SO4 aqueous solution was 97.46%.

[0050] Example 2

[0051] To prepare the crystallization-assisted high-flux nanofiltration membrane, all the following steps without temperature indication were carried out at room temperature.

[0052] (1) A polyethersulfone (PES) membrane with a size of 6 cm × 6 cm and a molecular weight cutoff of 100 KDa was pretreated by soaking it in deionized water for 48 h. The deionized water needed to be replaced every 12 h.

[0053] (2) 0.1 g of sodium hypophosphite was mixed with 99.9 g of deionized water to prepare a salt solution with a sodium hypophosphite concentration of 0.1 wt %.

[0054] (3) 0.2 g of trans-2,5-dimethylpiperazine was mixed with 99.8 g of deionized water to prepare a trans-2,5-dimethylpiperazine solution having a trans-2,5-dimethylpiperazine concentration of 0.2 wt %; the salt solution and the trans-2,5-dimethylpiperazine solution were mixed in equal proportions to prepare an aqueous phase solution having a sodium hypophosphite concentration of 0.05 wt % and a trans-2,5-dimethylpiperazine concentration of 0.1 wt %.

[0055] (4) 0.3 g of 1,3,5-benzenetricarboxylic acid chloride and 199.7 g of n-hexane solvent were mixed to prepare an organic phase solution having a 1,3,5-benzenetricarboxylic acid chloride concentration of 0.15 wt %.

[0056] (5) Adjust the temperature of the organic phase to -10°C; immerse the pretreated polyethersulfone membrane in the prepared aqueous phase solution and take it out after 5 minutes. Dry the residual moisture on the membrane surface with a rubber roller, and then put it into the organic phase solution for interfacial polymerization. Take it out after 0.5 minutes and put it into a 20°C constant temperature drying oven. After 2 minutes, a crystallization-assisted high-flux nanofiltration membrane is obtained.

[0057] The dried crystallization-assisted high-flux nanofiltration membrane was taken out and sealed in a water environment for measurement. Under a pressure of 0.2Mpa, the performance of the prepared crystallization-assisted high-flux nanofiltration membrane was tested with pure water, 2000ppm Na2SO4 aqueous solution, and 2000ppm Na2SO4 aqueous solution. The test results showed that the pure water permeability of the crystallization-assisted high-flux nanofiltration membrane was 37.45L·m-2h-1bar-1, and the retention rate of Na2SO4 aqueous solution was 96.32%.

[0058] Example 3

[0059] To prepare the crystallization-assisted high-flux nanofiltration membrane, all the following steps without temperature indication were carried out at room temperature.

[0060] (1) A polyethersulfone (PES) membrane with a size of 6 cm × 6 cm and a molecular weight cutoff of 100 KDa was pretreated by soaking it in deionized water for 48 h. The deionized water needed to be replaced every 12 h.

[0061] (2) 0.1 g of sodium hypophosphite was mixed with 99.9 g of deionized water to prepare a salt solution with a sodium hypophosphite concentration of 0.1 wt %.

[0062] (3) 0.2 g of trans-2,5-dimethylpiperazine was mixed with 99.8 g of deionized water to prepare a trans-2,5-dimethylpiperazine solution having a trans-2,5-dimethylpiperazine concentration of 0.2 wt %; the salt solution and the trans-2,5-dimethylpiperazine solution were mixed in equal proportions to prepare an aqueous phase solution having a sodium hypophosphite concentration of 0.05 wt % and a trans-2,5-dimethylpiperazine concentration of 0.1 wt %.

[0063] (4) 0.3 g of 1,3,5-benzenetricarboxylic acid chloride and 199.7 g of n-hexane solvent were mixed to prepare an organic phase solution having a 1,3,5-benzenetricarboxylic acid chloride concentration of 0.15 wt %.

[0064] (5) Adjust the temperature of the organic phase to -15°C; immerse the pretreated polyethersulfone membrane in the prepared aqueous phase solution and take it out after 5 minutes. Use a rubber roller to dry the residual moisture on the membrane surface, and then put it into the organic phase solution for interfacial polymerization. Take it out after 0.5 minutes and put it into a 20°C constant temperature drying oven. After 2 minutes, a crystallization-assisted high-flux nanofiltration membrane is obtained.

[0065] The dried crystallization-assisted high-flux nanofiltration membrane was taken out and sealed in a water environment for measurement. The performance of the prepared crystallization-assisted high-flux nanofiltration membrane was tested with pure water, 2000ppm Na2SO4 aqueous solution and 2000ppm Na2SO4 aqueous solution at a pressure of 0.2Mpa. The test results showed that the pure water permeability of the crystallization-assisted high-flux nanofiltration membrane was 39.16L·m-2h-1bar-1, and the retention rate of Na2SO4 aqueous solution was 96.88%.

[0066] Example 4

[0067] To prepare the crystallization-assisted high-flux nanofiltration membrane, all the following steps without temperature indication were carried out at room temperature.

[0068] (1) A polyethersulfone (PES) membrane with a size of 6 cm × 6 cm and a molecular weight cutoff of 100 KDa was pretreated by soaking it in deionized water for 48 h. The deionized water needed to be replaced every 12 h.

[0069] (2) 10 g of sodium hypophosphite was mixed with 90 g of deionized water to prepare a salt solution with a sodium hypophosphite concentration of 10 wt %.

[0070] (3) 0.2 g of trans-2,5-dimethylpiperazine was mixed with 99.8 g of deionized water to prepare a trans-2,5-dimethylpiperazine solution having a trans-2,5-dimethylpiperazine concentration of 0.2 wt %; the salt solution and the trans-2,5-dimethylpiperazine solution were mixed in equal proportions to prepare an aqueous solution having a sodium hypophosphite concentration of 5 wt % and a trans-2,5-dimethylpiperazine concentration of 0.1 wt %.

[0071] (4) 0.3 g of 1,3,5-benzenetricarboxylic acid chloride and 199.7 g of n-hexane solvent were mixed to prepare an organic phase solution having a 1,3,5-benzenetricarboxylic acid chloride concentration of 0.15 wt %.

[0072] (5) Adjust the temperature of the organic phase to -15°C; immerse the pretreated polyethersulfone membrane in the prepared aqueous phase solution and take it out after 5 minutes. Use a rubber roller to dry the residual moisture on the membrane surface, and then put it into the organic phase solution for interfacial polymerization. Take it out after 0.5 minutes and put it into a 20°C constant temperature drying oven. After 2 minutes, a crystallization-assisted high-flux nanofiltration membrane is obtained.

[0073] The dried crystallization-assisted high-flux nanofiltration membrane was taken out and sealed in a water environment for measurement. The performance of the prepared crystallization-assisted high-flux nanofiltration membrane was tested with pure water, 2000ppm Na2SO4 aqueous solution and 2000ppm Na2SO4 aqueous solution at a pressure of 0.2Mpa. The test results showed that the pure water permeability of the crystallization-assisted high-flux nanofiltration membrane was 40.20L·m-2h-1bar-1, and the retention rate of Na2SO4 aqueous solution was 95.99%.

[0074] Example 5

[0075] To prepare the crystallization-assisted high-flux nanofiltration membrane, all the following steps without temperature indication were carried out at room temperature.

[0076] (1) A polyethersulfone (PES) membrane with a size of 6 cm × 6 cm and a molecular weight cutoff of 100 KDa was pretreated by soaking it in deionized water for 48 h. The deionized water needed to be replaced every 12 h.

[0077] (2) 3 g of sodium hypophosphite was mixed with 97 g of deionized water to prepare a salt solution with a sodium hypophosphite concentration of 3 wt %.

[0078] (3) 0.2 g of trans-2,5-dimethylpiperazine was mixed with 99.8 g of deionized water to prepare a trans-2,5-dimethylpiperazine solution having a trans-2,5-dimethylpiperazine concentration of 0.2 wt %; the salt solution and the trans-2,5-dimethylpiperazine solution were mixed in equal proportions to prepare an aqueous solution having a sodium hypophosphite concentration of 1.5 wt % and a trans-2,5-dimethylpiperazine concentration of 0.1 wt %.

[0079] (4) 0.3 g of 1,3,5-benzenetricarboxylic acid chloride and 199.7 g of n-hexane solvent were mixed to prepare an organic phase solution having a 1,3,5-benzenetricarboxylic acid chloride concentration of 0.15 wt %.

[0080] (5) Adjust the temperature of the organic phase to -15°C; immerse the pretreated polyethersulfone membrane in the prepared aqueous phase solution and take it out after 5 minutes. Use a rubber roller to dry the residual moisture on the membrane surface, and then put it into the organic phase solution for interfacial polymerization. Take it out after 0.5 minutes and put it into a 20°C constant temperature drying oven. After 2 minutes, a crystallization-assisted high-flux nanofiltration membrane is obtained.

[0081] The dried crystallization-assisted high-flux nanofiltration membrane was taken out and sealed in a water environment for measurement. The performance of the prepared crystallization-assisted high-flux nanofiltration membrane was tested with pure water, 2000ppm Na2SO4 aqueous solution and 2000ppm Na2SO4 aqueous solution at a pressure of 0.2Mpa. The test results showed that the pure water permeability of the crystallization-assisted high-flux nanofiltration membrane was 45.31L·m-2h-1bar-1, and the retention rate of Na2SO4 aqueous solution was 96.83%.

[0082] Comparative Example 1

[0083] For the preparation of nanofiltration membranes, all the following steps without temperature indication were carried out at room temperature.

[0084] (1) A polyethersulfone (PES) membrane with a size of 6 cm × 6 cm and a molecular weight cutoff of 100 KDa was pretreated by soaking it in deionized water for 48 h. The deionized water needed to be replaced every 12 h.

[0085] (2) 3 g of sodium sulfate was mixed with 97 g of deionized water to prepare a salt solution with a sodium sulfate concentration of 3 wt %.

[0086] (3) 0.2 g of trans-2,5-dimethylpiperazine was mixed with 99.8 g of deionized water to prepare a trans-2,5-dimethylpiperazine solution having a trans-2,5-dimethylpiperazine concentration of 0.2 wt %; the salt solution and the trans-2,5-dimethylpiperazine solution were mixed in equal proportions to prepare an aqueous phase solution having a sodium sulfate concentration of 1.5 wt % and a trans-2,5-dimethylpiperazine concentration of 0.1 wt %.

[0087] (4) 0.3 g of 1,3,5-benzenetricarboxylic acid chloride and 199.7 g of n-hexane solvent were mixed to prepare an organic phase solution having a 1,3,5-benzenetricarboxylic acid chloride concentration of 0.15 wt %.

[0088] (5) Adjust the temperature of the organic phase to -15°C; immerse the pretreated polyethersulfone membrane in the prepared aqueous phase solution and take it out after 5 minutes. Use a rubber roller to dry the residual moisture on the membrane surface, and then put it into the organic phase solution for interfacial polymerization. Take it out after 0.5 minutes and put it into a 20°C constant temperature drying oven. After 2 minutes, a crystallization-assisted high-flux nanofiltration membrane is obtained.

[0089] The dried crystallization-assisted high-flux nanofiltration membrane was taken out and sealed in a water environment for measurement. The performance of the prepared crystallization-assisted high-flux nanofiltration membrane was tested with pure water, 2000ppm Na2SO4 aqueous solution and 2000ppm Na2SO4 aqueous solution at a pressure of 0.2Mpa. The test results showed that the pure water permeability of the crystallization-assisted high-flux nanofiltration membrane was 40.47L·m-2h-1bar-1, and the retention rate of Na2SO4 aqueous solution was 95.14%.

[0090] Comparative Example 2

[0091] For the preparation of nanofiltration membranes, all the following steps without temperature indication were carried out at room temperature.

[0092] (1) A polyethersulfone (PES) membrane with a size of 6 cm × 6 cm and a molecular weight cutoff of 100 KDa was pretreated by soaking it in deionized water for 48 h. The deionized water needed to be replaced every 12 h.

[0093] (2) 3 g of sodium bicarbonate was mixed with 97 g of deionized water to prepare a salt solution with a sodium bicarbonate concentration of 3 wt %.

[0094] (3) 0.2 g of trans-2,5-dimethylpiperazine was mixed with 99.8 g of deionized water to prepare a trans-2,5-dimethylpiperazine solution having a trans-2,5-dimethylpiperazine concentration of 0.2 wt %; the salt solution and the trans-2,5-dimethylpiperazine solution were mixed in equal proportions to prepare an aqueous phase solution having a sodium sulfate concentration of 1.5 wt % and a trans-2,5-dimethylpiperazine concentration of 0.1 wt %.

[0095] (4) 0.3 g of 1,3,5-benzenetricarboxylic acid chloride and 199.7 g of n-hexane solvent were mixed to prepare an organic phase solution having a 1,3,5-benzenetricarboxylic acid chloride concentration of 0.15 wt %.

[0096] (5) Adjust the temperature of the organic phase to -15°C; immerse the pretreated polyethersulfone membrane in the prepared aqueous phase solution and take it out after 5 minutes. Use a rubber roller to dry the residual moisture on the membrane surface, and then put it into the organic phase solution for interfacial polymerization. Take it out after 0.5 minutes and put it into a 20°C constant temperature drying oven. After 2 minutes, a crystallization-assisted high-flux nanofiltration membrane is obtained.

[0097] The dried crystallization-assisted high-flux nanofiltration membrane was taken out and sealed in a water environment for measurement. The performance of the prepared crystallization-assisted high-flux nanofiltration membrane was tested with pure water, 2000ppm Na2SO4 aqueous solution and 2000ppm Na2SO4 aqueous solution at a pressure of 0.2Mpa. The test results showed that the pure water permeability of the crystallization-assisted high-flux nanofiltration membrane was 29.23L·m-2h-1bar-1, and the retention rate of Na2SO4 aqueous solution was 83.42%.

[0098] Comparative Example 3

[0099] For the preparation of nanofiltration membranes, all the following steps without temperature indication were carried out at room temperature.

[0100] (1) A polyethersulfone (PES) membrane with a size of 6 cm × 6 cm and a molecular weight cutoff of 100 KDa was pretreated by soaking it in deionized water for 48 h. The deionized water needed to be replaced every 12 h.

[0101] (2) 3 g of sodium hypophosphite was mixed with 97 g of deionized water to prepare a salt solution with a sodium hypophosphite concentration of 3 wt %.

[0102] (3) 0.2 g of piperazine was mixed with 99.8 g of deionized water to prepare a piperazine solution having a piperazine concentration of 0.2 wt %; the salt solution and the piperazine solution were mixed in equal proportions to prepare an aqueous solution having a sodium hypophosphite concentration of 1.5 wt % and a piperazine concentration of 0.1 wt %.

[0103] (4) 0.3 g of 1,3,5-benzenetricarboxylic acid chloride and 199.7 g of n-hexane solvent were mixed to prepare an organic phase solution having a 1,3,5-benzenetricarboxylic acid chloride concentration of 0.15 wt %.

[0104] (5) Adjust the temperature of the organic phase to -15°C; immerse the pretreated polyethersulfone membrane in the prepared aqueous phase solution and take it out after 5 minutes. Use a rubber roller to dry the residual moisture on the membrane surface, and then put it into the organic phase solution for interfacial polymerization. Take it out after 0.5 minutes and put it into a 20°C constant temperature drying oven. After 2 minutes, a crystallization-assisted high-flux nanofiltration membrane is obtained.

[0105] The dried crystallization-assisted high-flux nanofiltration membrane was taken out and sealed in a water environment for measurement. The performance of the prepared crystallization-assisted high-flux nanofiltration membrane was tested with pure water, 2000ppm Na2SO4 aqueous solution and 2000ppm Na2SO4 aqueous solution at a pressure of 0.2Mpa. The test results showed that the pure water permeability of the crystallization-assisted high-flux nanofiltration membrane was 27.97L·m-2h-1bar-1, and the retention rate of Na2SO4 aqueous solution was 95.64%.

[0106] Comparative Example 4

[0107] For the preparation of nanofiltration membranes, all the following steps without temperature indication were carried out at room temperature.

[0108] (1) A polyethersulfone (PES) membrane with a size of 6 cm × 6 cm and a molecular weight cutoff of 100 KDa was pretreated by soaking it in deionized water for 48 h. The deionized water needed to be replaced every 12 h.

[0109] (2) 3 g of sodium hypophosphite was mixed with 97 g of deionized water to prepare a salt solution with a sodium hypophosphite concentration of 3 wt %.

[0110] (3) 0.2 g of trans-2,5-dimethylpiperazine was mixed with 99.8 g of deionized water to prepare a trans-2,5-dimethylpiperazine solution having a trans-2,5-dimethylpiperazine concentration of 0.2 wt %; the salt solution and the trans-2,5-dimethylpiperazine solution were mixed in equal proportions to prepare an aqueous solution having a sodium hypophosphite concentration of 1.5 wt % and a trans-2,5-dimethylpiperazine concentration of 0.1 wt %.

[0111] (4) 0.3 g of 1,3,5-benzenetricarboxylic acid chloride and 199.7 g of n-hexane solvent were mixed to prepare an organic phase solution having a 1,3,5-benzenetricarboxylic acid chloride concentration of 0.15 wt %.

[0112] (5) Adjust the temperature of the organic phase to -15°C; immerse the pretreated polyethersulfone membrane in the prepared aqueous phase solution and take it out after 5 minutes. Dry the residual moisture on the membrane surface with a rubber roller, and then put it into the organic phase solution for interfacial polymerization. Take it out after 0.5 minutes and put it into a 50°C constant temperature drying oven. After 1 minute, a crystallization-assisted high-flux nanofiltration membrane is obtained.

[0113] The dried crystallization-assisted high-flux nanofiltration membrane was taken out and sealed in a water environment for measurement. The performance of the prepared crystallization-assisted high-flux nanofiltration membrane was tested with pure water, 2000ppm Na2SO4 aqueous solution and 2000ppm Na2SO4 aqueous solution at a pressure of 0.2Mpa. The test results showed that the pure water permeability of the crystallization-assisted high-flux nanofiltration membrane was 30.39L·m-2h-1bar-1, and the retention rate of Na2SO4 aqueous solution was 95.08%.

[0114] Comparative Example 5

[0115] For the preparation of nanofiltration membranes, all the following steps without temperature indication were carried out at room temperature.

[0116] (1) A polyethersulfone (PES) membrane with a size of 6 cm × 6 cm and a molecular weight cutoff of 100 KDa was pretreated by soaking it in deionized water for 48 h. The deionized water needed to be replaced every 12 h.

[0117] (2) 3 g of sodium hypophosphite was mixed with 97 g of deionized water to prepare a salt solution with a sodium hypophosphite concentration of 3 wt %.

[0118] (3) 0.2 g of trans-2,5-dimethylpiperazine was mixed with 99.8 g of deionized water to prepare a trans-2,5-dimethylpiperazine solution having a trans-2,5-dimethylpiperazine concentration of 0.2 wt %; the salt solution and the trans-2,5-dimethylpiperazine solution were mixed in equal proportions to prepare an aqueous solution having a sodium hypophosphite concentration of 1.5 wt % and a trans-2,5-dimethylpiperazine concentration of 0.1 wt %.

[0119] (4) 0.3 g of 1,3,5-benzenetricarboxylic acid chloride and 199.7 g of n-hexane solvent were mixed to prepare an organic phase solution having a 1,3,5-benzenetricarboxylic acid chloride concentration of 0.15 wt %.

[0120] (5) Adjust the temperature of the organic phase to 20°C; immerse the pretreated polyethersulfone membrane in the prepared aqueous phase solution and take it out after 5 minutes. Dry the residual moisture on the membrane surface with a rubber roller, and then put it into the organic phase solution for interfacial polymerization. Take it out after 0.5 minutes and put it into a 20°C constant temperature drying oven. After 1 minute, a crystallization-assisted high-flux nanofiltration membrane is obtained.

[0121] The dried crystallization-assisted high-flux nanofiltration membrane was taken out and sealed in a water environment for measurement. The performance of the prepared crystallization-assisted high-flux nanofiltration membrane was tested with pure water, 2000ppm Na2SO4 aqueous solution and 2000ppm Na2SO4 aqueous solution at a pressure of 0.2Mpa. The test results showed that the pure water permeability of the crystallization-assisted high-flux nanofiltration membrane was 32.72L·m-2h-1bar-1, and the retention rate of Na2SO4 aqueous solution was 96.56%.

[0122] In summary, the pure water permeability of the crystallization-assisted high-flux nanofiltration membrane prepared in Example 5 of the present invention is 45.31 L·m-2h-1bar-1, and the retention rate of Na2SO4 aqueous solution is 96.83%. The comprehensive consideration of water flux and the retention rate of Na2SO4 aqueous solution is significantly higher than that of the control example.

[0123] The phrases "one embodiment", "an embodiment", etc. mentioned in the specification indicate that the embodiment described may include a specific feature, structure or characteristic, but not every embodiment may include the specific feature, structure or characteristic. In addition, such phrases do not necessarily refer to the same embodiment. In addition, when a specific feature, structure or characteristic is described in conjunction with an embodiment, it is within the knowledge of those skilled in the art to implement such feature, structure or characteristic in conjunction with other embodiments, whether explicitly or not explicitly described.

[0124] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.

[0125] The above description is only a preferred embodiment of the present disclosure and is not intended to limit the present disclosure. Any modifications, equivalent substitutions, etc. made within the spirit and principles of the present disclosure should be included in the protection scope of the present disclosure.

Claims

1. A method for preparing a crystallization-assisted high-flux nanofiltration membrane, characterized in that: The following steps are involved: Pretreatment of nanofiltration base membrane; Prepare a salt solution with sodium hypophosphite; The trans-2,5-dimethylpiperazine is prepared into a trans-2,5-dimethylpiperazine solution, and then the salt solution is mixed with the trans-2,5-dimethylpiperazine solution to prepare an aqueous phase solution; Mixing 1,3,5-benzenetricarboxylic acid chloride and n-hexane solvent to prepare an organic phase solution; The pretreated nanofiltration base membrane is placed in an aqueous solution, taken out, dried, and then placed in a low-temperature organic solution for low-temperature interfacial polymerization, taken out and dried again to obtain a crystallization-assisted high-flux nanofiltration membrane.

2. The method for preparing a crystallization-assisted high-flux nanofiltration membrane according to claim 1, characterized in that: The nanofiltration base membrane is made of polyethersulfone.

3. The method for preparing a crystallization-assisted high-flux nanofiltration membrane according to claim 1, characterized in that: The membrane cut-off molecular weight of the nanofiltration base membrane is greater than 50 KDa and less than 150 KDa.

4. The method for preparing a crystallization-assisted high-flux nanofiltration membrane according to claim 1, characterized in that: The pretreatment of the nanofiltration base membrane comprises: The nanofiltration base membrane was immersed in deionized water at 15°C-30°C for 48h-98h, and the deionized water was replaced every 6h-12h.

5. The method for preparing a crystallization-assisted high-flux nanofiltration membrane according to claim 1, characterized in that: The concentration of the sodium hypophosphite is 0.01wt%-5.00wt%.

6. The method for preparing a crystallization-assisted high-flux nanofiltration membrane according to claim 1, characterized in that: The concentration of the trans-2,5-dimethylpiperazine is 0.05 wt % to 1.00 wt %.

7. The method for preparing a crystallization-assisted high-flux nanofiltration membrane according to claim 1, characterized in that: The concentration of 1,3,5-benzenetricarboxylic acid chloride in the organic phase solution is 0.025 wt % to 0.25 wt %.

8. The method for preparing a crystallization-assisted high-flux nanofiltration membrane according to claim 1, characterized in that: In the step of placing the pretreated nanofiltration base membrane into an aqueous solution, taking it out and drying it, then placing it into a low-temperature organic solution for low-temperature interfacial polymerization, taking it out and drying it again to obtain a crystallization-assisted high-flux nanofiltration membrane, the temperature of the organic solution is adjusted to -15°C-20°C.

9. The method for preparing a crystallization-assisted high-flux nanofiltration membrane according to claim 1, characterized in that: In the step of placing the pretreated nanofiltration base membrane into the aqueous solution, the nanofiltration base membrane stays in the aqueous solution for 2 minutes to 7 minutes, the interfacial polymerization reaction lasts for 20 seconds to 120 seconds, and the drying is performed by rubber roller drying.

10. The method for preparing a crystallization-assisted high-flux nanofiltration membrane according to claim 1, characterized in that: The membrane is taken out and dried again to obtain a crystallization-assisted high-flux nanofiltration membrane. The time for the second drying is 0.5 min-2.5 min, and the temperature for the second drying is 20° C.-80° C.

Citation Information

Patent Citations

  • Composite membrane as well as preparation method and application thereof

    CN117654287A

  • High-flux anti-pollution composite nanofiltration membrane and preparation method thereof

    CN118767705A

  • Mntbap for use in inducing a transient immune tolerance

    EP3431088A1

  • Thin-Film Composite Membranes Synthesized by Multi-Step Coating Methods

    US20230182087A1

  • Reactive support layer-based separation membrane, preparation method, and application

    WO2023179530A1